1993
DOI: 10.3181/00379727-204-43658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immobilization Stress on Plasma Luteinizing Hormone, Testosterone, and Corticosterone Concentrations and on 3 -Hydroxysteroid Dehydrogenase Activity in the Testes of Adult Rats

Abstract: We have examined the effect of 3 hr of immobilization stress on plasma luteinizing hormone, testosterone, and corticosterone levels, and on the activity of 3Bhydroxysteroid dehydrogenase (38-HSD) in microsomal and mitochondria1 fractions of the testis from adult rats. Immobilization for 3 hr increased plasma corticosterone and reduced plasma testosterone concentrations by 57%. Plasma luteinizing hormone levels were lower, although not significantly (P = 0.093) so, in stressed animals. Immobilization (3 hr) red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 6 publications
2
32
1
1
Order By: Relevance
“…The ability of stress to inhibit reproductive function is well documented (27,28,37,38,39,40,50,55,56,64,72). A sharp decline of serum testosterone is one of the first signs of IMO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of stress to inhibit reproductive function is well documented (27,28,37,38,39,40,50,55,56,64,72). A sharp decline of serum testosterone is one of the first signs of IMO.…”
Section: Discussionmentioning
confidence: 99%
“…17), whereas other investigators reported a stimulatory effect of this peptide on steroidogenesis in the mouse testis (29,33). It is well documented that plasma levels of CRH and glucocorticoids increase during stress (30,31,32,55,56,72) and that adrenal glucocorticoids may mediate some of the effects of acute stress on the gonadal axis (24,26,27,28,32,55). Because one determinant in setting the level of glucocorticoid activity in Leydig cells is whether the steroid is metabolized, we followed the expression 11␤HSD transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after the end of 2-to 3-h stress sessions, serum androgens, but not gonadotropins, are reduced (Orr & Mann 1992, Srivastava et al 1993, Akinbami et al 1994, Maric et al 1996, Kostic et al 1997, 1998a. The stress-induced decrease in serum androgens is accompanied by significant changes in the activities of two steroidogenic enzymes, 3 -hydroxysteroid dehydrogenase (3 HSD) and 17 -hydroxylase/C17-20 lyase (P450c17) (Srivastava et al 1993, Akinbami et al 1994, Maric et al 1996, Kostic et al 1997, 1998a. In vitro androgenesis by decapsulated testes from stressed rats exposed to human chorionic gonadotropin (hCG) for 3 h is also reduced, and this reduction coincides with an elevation in the testicular nitrite levels, a stable oxidation product of the nitric oxide pathway (Kostic et al 1998b).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, TNF-a acutely elevates glucocorticoid levels [8,10]. Increased glucocorticoids causes primary hypogonadism and diminish androgen production [9,13]. Increased glucocorticoids and reduced androgen levels induce testicular germ cell apoptosis [13].…”
Section: Resultsmentioning
confidence: 99%